2020
DOI: 10.1108/jadee-03-2019-0033
|View full text |Cite
|
Sign up to set email alerts
|

Market arrival of apples under risk in Jammu & Kashmir, India: evidence from an ARDL application

Abstract: PurposeThe purpose of this paper is to examine the market response of apple growers to price and price risk along with weather factors and weather risk in the state of Jammu & Kashmir. In other words, it tries to find the both short-run and long-run price elasticities of apples' market arrival and also the elasticity with respect to price-risk and weather-risk variables.Design/methodology/approachThis paper uses the bound test approach of “auto-regressive distributed lag” (ARDL) model. Monthly data on mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 18 publications
(26 reference statements)
0
7
0
Order By: Relevance
“…Like other studies of apple farmers (e.g. Akber and Paltasingh, 2020), apple farmers in our sample are risk-averse. We also find that intertemporal decision-making of marketing is moderately associated with the degree of risk-seeking under the gain scenario but not with time preference.…”
Section: Conclusion and Policy Implicationsmentioning
confidence: 70%
See 1 more Smart Citation
“…Like other studies of apple farmers (e.g. Akber and Paltasingh, 2020), apple farmers in our sample are risk-averse. We also find that intertemporal decision-making of marketing is moderately associated with the degree of risk-seeking under the gain scenario but not with time preference.…”
Section: Conclusion and Policy Implicationsmentioning
confidence: 70%
“…Experiment design of risk attitude and time preference Because of the perishability of apples and the importance of storage to the crop (Akber and Paltasingh, 2020), we are interested in understanding the role of farmers' risk and time preferences relating to storage and intertemporal sales. To this end, we introduce multiple list methods and elicitation strategies to measure risk attitudes and time preference through two separate field experiments.…”
Section: Research Design Methods and Data Collectionmentioning
confidence: 99%
“…This framework has been used in several studies (e.g. Kumar et al, 2021;Mustapha and Said, 2016;Akber and Paltasingh, 2020;Chopra, 2022). Prior to estimating the ARDL framework, the authors tested the unit root status of the variables, with and without structural breaks.…”
Section: Analytical Frameworkmentioning
confidence: 99%
“…Findings revealed a negative and significant linkage between CO 2 emissions and economic growth, while there is a positive and significant association between agricultural output and economic growth. Akber and Paltasingh (2020) examined the market response of apple growers to price-risk along with weather-risk in the state of Jammu and Kashmir, India. Using the ARDL bounds testing approach, the study confirmed the existence of the long-run relationship between the price elasticities of apples' market arrival and also the elasticity concerning price-risk and weather-risk variables.…”
Section: Theoretical Background and Literature Reviewmentioning
confidence: 99%